Pengaruh Model Pembelajaran Inkuiri Terbimbing Berbantuan Kahoot Untuk Meningkatkan Hasil Belajar Peserta Didik SMA Pada Materi Energi Terbarukan - Harianja, Eliza Crystiani; Nainggolan, Juliper; Surbakti, Mariana (Jurnal Kajian Ilmu Pendidikan (JKIP), 2025)
This research aims to determine the effect of the Kahoot-assisted guided inquiry model to improve high school students' learning outcomes in class X renewable energy material at SMA Parulian 2 Medan. The method used is quasi-experimental with a nonequivalent control group design. Sampling was carried out using purposive sampling technique. The research samples for experimental class X-B and control class X-A each consisted of 28 students. The instrument used is a learning outcomes test, multiple choice with 20 questions. Before being given treatment, a prerequisite test must be carried out to determine whether the sample comes from a population that is normally distributed and homogeneous. Furthermore, the pretest was given to the experimental and control classes with average scores of 52.85 and 51.78 respectively with standard deviations of 16.36 and 13.69. After being given treatment in the experimental and control classes, by giving a posttest an average score of 65.53 and 66.42 was obtained with a standard deviation of 12.57 and 10.35. To determine the differences between the two classes, a one-sided t-test was carried out with α=0.05, it was found that t-hitung > t-tabel, which indicated that there was a significant difference in science process skills in Newton's law material.